1996
DOI: 10.1007/bf01857602
|View full text |Cite
|
Sign up to set email alerts
|

The effects of caffeine on ambulatory blood pressure, heart rate, and mood in coffee drinkers

Abstract: The present study examined the effects of caffeine, as typically ingested through coffee, on ambulatory systolic and diastolic blood pressure (BP), heart rate, and mood. Normotensive coffee drinkers wore a BP monitor for two 24-hr periods, consuming decaffeinated coffee. Each cup was supplemented with 125 mg caffeine or cornstarch. Systolic and diastolic BPs were elevated on the day caffeine was consumed (maximum, 3.6 and 5.6 mm Hg, respectively), most notably shortly after ingestion. Heart rate was higher ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 47 publications
2
28
1
1
Order By: Relevance
“…Caffeine has been classically regarded as an inducer of anxiety at higher doses, typically over 300 mg [10,24,27,28], but the consumption of caffeine is poorly correlated with anxiety or anxiety traits [17,29,30]. Besides dosage, the anxiogenic effect of caffeine is influenced by individual factors, such as preference for caffeine, presence of some anxiety disorders, and genetic background.…”
Section: S241mentioning
confidence: 99%
“…Caffeine has been classically regarded as an inducer of anxiety at higher doses, typically over 300 mg [10,24,27,28], but the consumption of caffeine is poorly correlated with anxiety or anxiety traits [17,29,30]. Besides dosage, the anxiogenic effect of caffeine is influenced by individual factors, such as preference for caffeine, presence of some anxiety disorders, and genetic background.…”
Section: S241mentioning
confidence: 99%
“…Daytime ambulatory blood pressure has generally been higher on caffeine days than on caffeine-free days (Jeong & Dimsdale 1990;James 1994;Superko et al, 1994;Green & Suls, 1996;Lane et al, 1998;Rakic et al, 1999), whereas some studies which reported ambulatory blood pressure recordings as 24 h means have failed to detect this pressor effect (MacDonald et al, 1991;Eggertsen et al, 1993) (Table 4).…”
Section: Acute Intake Of Coffee or Caffeine And Blood Pressurementioning
confidence: 99%
“…The pressor response has been reported as diminishing within a few days of the start of regular intake of caffeine (Robertson et al, 1981(Robertson et al, , 1984Ammon et al, 1983;Myers & Reeves, 1991). However, the tolerance may be partial, because in some studies caffeine was still able to elevate blood pressure during habitual consumption (Burr et al, 1989;Jeong & Dimsdale 1990;James 1994;Green & Suls, 1996). The pressor response to caffeine may be regained after a relatively short period of abstinence.…”
Section: Acute Intake Of Coffee or Caffeine And Blood Pressurementioning
confidence: 99%
“…Caffeine enhances physiological arousal, by activating both the sympathetic nervous system by increasing heart rate and blood pressure (Davidson and Smith 1991;Green and Suls 1996;James and Gregg 2004) and the hypothalamic pituitary adrenal axis by increasing cortisol (Lovallo et al 1996(Lovallo et al , 2005. Caffeine exerts physiological effects similar to those of acute stress (Gerra et al 2001;Kudielka et al 2004) and may augment the physiological stress response (Lovallo et al 2006).…”
Section: Introductionmentioning
confidence: 99%